Betel Nut Husks as An Alternative Litter Materials for Broiler Production - Azis , A.; Zubaidah; Afriani (International Journal of Poultry Science, 2020)
Background and Objective: The availability of rice hulls has become infrequent due to competition and the development of residual rice byproducts; therefore, it has forced farmers to seek alternative litter materials. The objective of this study was to investigate the effect of using betel nut husks compared to rice hulls or dried leaves as litter material for broiler production on productive performance, carcass traits and internal organ characteristics. Materials and Methods: A total of 270 unsexed one-day-old broiler chicks (Lohmann) were included the study; a completely randomized design including three treatments with six replicates consisting of 15 chicks each was applied. The treatments comprised betel nut husks, rice hulls and dried leaves as litter materials. Standard feeding and management practices were followed during the experimental period. The body weight and feed intake were recorded weekly and the body weight gain and feed conversion ratio were calculated. Two broilers from each pen were used to measure the carcass traits, abdominal fat pad quantity and internal organ weight at 35 day of age. Results: The results from the present study showed that the litter materials did not affect (p>0.05) body weight gain, feed intake and feed conversion ratios during the experimental period. The carcass yield and abdominal fat quantity were not influenced (p>0.05) by the litter material. There was no difference (p>0.05) among the three litter materials in the internal organ weight; however, the gizzard weight was higher (p<0.05) in the broilers reared on rice hulls than in those reared on dried leaves and betel nut husks. Conclusion: Betel nut husks can be used as an alternative litter material for broiler production without sacrificing the performance of broiler chickens.